APLIKASI RHIZOPUS OLIGOSPORUS, RHIZOPUS ORYZAE, ISI TUBUH KEPITING DAN ENZIM BROMELIN PADA BIOEKSTRAKSI KRIM SANTAN KELAPA MENJADI VIRGIN COCONUT OIL - Kusumayanti, Heny; Susanti, Margaretha Tuti; Yulianto, Mohamad Endy (Universitas Diponegoro, 2006)
Abstract Oil production process with fermentation is one of method to produce virgin coconut oil (VICO). In this research, fermentation process done with coconut extract fermentation method as substrate, with biocatalysator, are Rhyzopus oligosporus, Rhyzopus orizae, body of crab and bromelin enzyme from raw pineapple. Design which used is a completed blocked random design. Source of variation is comparison of starter and substrate. From research which has done by biocatalysator, the most effective is Rhyzopus oligosporus with comparison starter and substrate 0,75 : 1, with velocity agitation 150 rpm, produce efficiency 90,23 % test of peroxide number until five weeks keep is 2,7-4,4, acid number 0,02, iod number 8,1, this result is comformable with food oil standard. Key words : coconut extract – fermentation – Virgin coconut oil (VICO)